Soil Physico-Chemical Properties Change Across an Urbanity Gradient in Berlin - Whitehead, James; Hempel, Stefan; Hiller, Anne; von der Lippe, Moritz; Rillig, Matthias C. (Frontiers in Environmental Science, 2021)
In this study the impacts of urbanity on physical soil properties were explored by measuring water stable aggregates, particle size, infiltration rate and hydrophobicity across an urban gradient. The use of a gradient allowed for the relative importance of different environmental drivers to be assessed. We sampled 54 sites across Berlin and used a pre-existing database of environmental variables to extract three main axes of variation relating to urbanity, soil nutrient content, and heavy metal content. These axes, along with site age, were used to explore the drivers of changes in physical properties across an urban landscape. The percentage of water stable aggregates was found to decrease with urbanity, whilst infiltration rate was found to increase. Hydrophobicity did not appear to be influenced by urbanity but interacted with both infiltration rate and water stable aggregates. Particle sizes in the soil were found to increase with urbanity. Our findings provide evidence for urbanity being an important driver of variation in physico-chemical soil properties.